A Passion to Preserve Gay Men as Keepers of Culture - Fellows, Will (University of Wisconsin Press, 2005)
From large cities to rural communities, gay men have long been impassioned pioneers as keepers of culture: rescuing and restoring decrepit buildings, revitalizing blighted neighborhoods, saving artifacts and documents of historical significance. A Passion to Preserve explores this authentic and complex dimension of gay men's lives by profiling early and contemporary preservationists from throughout the United States, highlighting contributions to the larger culture that gays are exceptionally inclined to make.